The Daunting Enterprise of the Law: Essays in Honour of Harry Arthurs - Archer, Simon; Zumbansen, Peer; Drache, Daniel (McGill-Queen's University Press, 2017)
Harry Arthurs, professor emeritus at Osgoode Hall Law School in Toronto and former president of York University, is one of the most widely respected scholars, educators, and policy makers in the world today. His enormous academic and institutional productivity has extended to administrative and labour law, legal pluralism and legal theory, legal education and institutional reform. This collection brings together essays, thought pieces, reminiscences and commentaries written in honour of Arthurs from scholars and colleagues from around the world whose work and thinking has been shaped by Arthurs' contributions over the years. --Publisher's description.
Keywords: Administrative Law & Regulatory Practice. LAW / General; Canada. LAW; Labor laws and legislation

The Mill: Fifty Years of Pulp and Protest - Baxter, Joan (Pottersfield Press, 2017)
The Mill - Fifty Years of Pulp and Protest explores the power that a single industry can wield. For fifty years, the pulp mill near Pictou in northern Nova Scotia has buoyed the local economy and found support from governments at all levels. But it has also pulped millions of acres of forests, spewed millions of tonnes of noxious emissions into the air, consumed quadrillions of litres of fresh water and then pumped them out again as toxic effluent into nearby Boat Harbour, and eventually into the Northumberland Strait. From the day it began operation in 1967, the mill has fomented protest and created deep divisions and tensions in northern Nova Scotia. This story is about people whose livelihoods depend on the pulp mill and who are willing to live with the "smell of money." It's about people whose well-being, health, homes, water, air, and businesses have been harmed by the mill's emissions and effluent. It's about the heartache such divisions cause and about people who, for the sake of peace, keep their thoughts about the mill to themselves. But it's also about hope, giving voice to those who led the successive groups that have protested and campaigned for a cleaner mill - First Nations, fishers, doctors, local councillors, tourism operators, artists and musicians, teachers and woodlot owners. Their personal stories are interwoven into a historical arc that traces the mill's origins and the persistent environmental and social problems it causes to this day. Baxter weaves a rich tapestry of storytelling, relevant to everyone who is concerned about how we can start to renegotiate the relationship between economy, jobs, and profits on one hand, and human well-being, health, and the environment on the other. The Mill tells a local story with global relevance and appeal. --Publisher's description
Keywords: Economic conditions; Environmental aspects; History; Northern Pulp (Pictou, N.S.); Nova Scotia Pictou; Pictou (N.S.); Pulp mills; Social aspects; Social conditions; Wood-pulp industry

Austerity: The Lived Experience - Evans, Brian; McBride, Stephen (University of Toronto Press, 2017)
Bryan M. Evans, Stephen McBride, and their contributors delve further into the more practical, ground-level side of the austerity equation in Austerity: The Lived Experience. Economically, austerity policies cannot be seen to work in the way elite interests claim that they do. Rather than soften the blow of the economic and financial crisis of 2008 for ordinary citizens, policies of austerity slow growth and lead to increased inequality. While political consent for such policies may have been achieved, it was reached amidst significant levels of disaffection and strong opposition to the extremes of austerity. The authors build their analysis in three sections, looking alternatively at theoretical and ideological dimensions of the lived experience of austerity; how austerity plays out in various public sector occupations and policy domains; and the class dimensions of austerity. The result is a ground-breaking contribution to the study of austerity politics and policies. Contents: Austerity as lived experience: An introduction / Bryan Evans and Stephen McBride. Pt. 1. Theory and ideology. Introduction: Manufacturing the common sense of austerity / Bryan Evans and McBride -- Articulating austerity and authoritarianism: Re-imagining moral economies? / John Clarke -- Speaking austerity: Policy rhetoric and design beyond fiscal consolidation / Sorin Mitrea -- No deal capitalism: Austerity and the unmaking of the North American middle class / Eric Pineault -- Framing the economic case for Austerity: The “expansionary fiscal contraction hypothesis” / Ellen Russell. Pt. 2. Impact and consequences. Introduction: Austerity on the ground / Evans and McBride -- Care and control in long term care work / Donna Baines -- ‘Negotiate your way back to zero’: Teacher bargaining and austerity in Ontario, Canada / Brendan A. Sweeny and Robert S. Hickey -- Austerity and the low wage economy: Living and other wages / Bryan Evans, Stephen McBride, and Jacob Muirhead -- Immigration in an age of austerity: Morality, the welfare state and the shaping of the ideal migrant / Susan Barrass and John Shields -- Pension reforms in the context of the global financial crisis: A reincarnation of pension privatization through austerity / Yanqiu Rachel Zhou and Shih-Jiun Shi. Pt. 3. Class, resistance, alternative. Introduction: The old strategies don’t work. So what’s possible? / Bryan Evans and Stephen McBride -- From austerity to structural reform: The erosion of the European social model(s) / Christophe Hermann -- Austerity of imagination: Quebec’s struggles in translating resistance into alternatives / Peter Graefe and Hubert Rioux -- Social democracy and social pacts: Austerity alliances and their consequences / Bryan Evans -- Austerity and political crisis: The radical left, the far right and Europe’s new authoritarian order / Neil Burron -- Conclusion.

Income Inequality: The Canadian Story - Green, David A.; Riddell, W. Craig; St-Hilaire, France (The Art of the State, 2017)
The Institute for Research on Public Policy, in collaboration with the Canadian Labour Market and Skills Researcher Network, has gathered some of the country’s leading experts to provide new evidence on the causes and effects of growing income inequality in Canada and the role of policy. Their research and analysis is collected in this volume, the fifth in the IRPP’s The Art of the State series. --Publisher's description
Keywords: American middle class; Culture; Economic inequality; Economics; Economy; Education; Employment; Gini coefficient; Human activities; Immigration

The Equity Myth: Racialization and Indigeneity at Canadian Universities - Henry, Frances; Kobayashi, Audrey Lynn; Smith, Malinda; Dua, Enakshi; James, Carl E.; Li, Peter; Ramos, Howard (UBC Press, 2017)
The university is often regarded as a bastion of liberal democracy where equity and diversity are vigorously promoted. In reality, the university still excludes many people and is a site of racialization that is subtle, complex, and sophisticated. This book, the first comprehensive, data-based study of racialized and Indigenous faculty members' experiences in Canadian universities, challenges the myth of equity in higher education. Drawing on a rich body of survey data, interviews, and analysis of universities' stated policies, leading scholars scrutinize what universities have done and question the effectiveness of their employment equity programs. They also make important recommendations as to how universities can address racialization and fulfill the promise of equity in the academy. --Publisher's description. Contents: Introduction : setting the context -- Representational analysis : comparing Canada, the United States, the United Kingdom, and Australia -- Differences in representation and employment income of racialized university professors in Canada -- Academic production, reward, and perceptions of racialized faculty members -- "Would never be hired these days" : the precarious work situation of racialized and indigenous faculty members -- The everyday world of racialized and indigenous faculty members in Canadian universities -- "You know why you were hired don't you?" Expectations and challenges in university appointments -- Shifting terrains : a picture of the institutionalization of equity in Canadian universities -- Mechanisms to address inequities in Canadian universities : the performativity of ineffectiveness -- Disciplinary silences : race, indigeneity, and gender in the social sciences -- A dirty dozen : unconscious race and gender biases in the academy -- Conclusion : challenging the myth. Includes bibliographical references (pages 328-355) and index.
Keywords: Canada Discrimination dans l'emploi; Canada Discrimination in employment. Discrimination in higher education. Equality. Indian college teachers. Race discrimination. Universities and colleges; Canada Discrimination raciale; Canada. Discrimination in employment; Canada. Discrimination in higher education; Canada. Equality; Canada. Race discrimination; Canada. Universities and colleges; Indian college teachers

Scarborough - Hernandez, Catherine (Arsenal Pulp Press, 2017)
A poignant, multi-voiced novel about life in the inner city. Scarborough is a low-income, culturally diverse neighbourhood east of Toronto, the fourth largest city in North America; like many inner-city communities, it suffers under the weight of poverty, drugs, crime, and urban blight. Scarborough the novel employs a multitude of voices to tell the story of a tight-knit neighbourhood under fire: among them, Victor, a black artist harassed by the police; Winsum, a West Indian restaurant owner struggling to keep it together; and Hina, a Muslim school worker who witnesses first-hand the impact of poverty on education. And then there are the three kids who work to rise above a system that consistently fails them: Bing, a gay Filipino boy who lives under the shadow of his father's mental illness; Sylvie, Bing's best friend, a Native girl whose family struggles to find a permanent home to live in; and Laura, whose history of neglect by her mother is destined to repeat itself with her father. Scarborough has already received recognition as winner of the Asian Canadian Writers' Workshop Emerging Writers Award in 2015, and finalist for the 2016 $50,000 Half the World Global Literati Award for best unpublished manuscript. It offers a raw yet empathetic glimpse into a troubled community that locates its dignity in unexpected places: a neighbourhood that refuses to be undone."-- Publisher's description
Keywords: Canadian fiction; Canadian fiction (English) 21st century; Fiction; Fictional Work; Ontario Scarborough; Pauvreté Romans, nouvelles, etc; Poverty; Poverty Fiction; Romans; Scarborough (Toronto, Ont.) Fiction

Workers' Compensation: Analysis for Its Second Century - Hunt, H. Allen; Dillender, Marcus (WE Focus Series, 2017)
Hunt and Dillender review the status of workers' compensation programs on three critical performance areas: 1) the adequacy of compensation for those disabled in the workplace, 2) return-to-work performance for injured workers, and 3) prevention of disabling injury and disease. [ Includes Canadian content.] --Publisher's abstract

Work and Labour in Canada: Critical Issues - Jackson, Andrew; Thomas, Mark P. (Canadian Scholars Press, 2017)
Over the last few decades, the workplace in Canada has experienced profound changes. Work has become increasingly insecure for a growing number of people, young workers struggle to match qualifications and credentials with jobs, and retirement with a secure income is a diminishing prospect. The demographic composition of the labour market is transforming, yet this change is conditioned by longstanding patterns of inequality in terms of gender, race, disability, and immigration status. This third edition of Work and Labour in Canada maps out major trends and patterns that define working life, and identifies the economic, social, and political factors that shape the contemporary workplace. While evaluating working conditions and job quality from a critical perspective, the authors point towards possibilities for a more equitable and democratic future of work. Thoroughly updated and featuring recommended readings, internet resources, and a new chapter on disability and work, this revised edition is an essential textbook for teachers, researchers, labour activists, and students of labour studies and sociology of work. --Publisher's description. Includes bibliographical references (pages 299-322) and index. Contents: The world of work in the 21st century -- Work, wages, and living standards in Canada -- Education, training, and lifelong learning : tensions and contradictions -- The unhealthy Canadian workplace -- Gender, work, and social reproduction -- Race, racialization, and racism at work -- The inaccessible Canadian workplace -- Troubled transitions : into and out of the labour force -- The impact of unions -- Workers' movements in the new millennium -- Globalization and work in Canada -- Improving work : reforming or transforming wage labour?

Spying on Canadians: The Royal Canadian Mounted Police Security Service and the Origins of the Long Cold War - Kealey, Gregory S. (University of Toronto Press, 2017)
Award-winning author Gregory S. Kealey's study of Canada's security and intelligence community before the end of World War II depicts a nation caught up in the Red Scare in the aftermath of the Bolshevik Revolution and tangled up with the imperial interests of first the United Kingdom and then the United States. Spying on Canadians brings together over twenty five years of research and writing about political policing in Canada. Through its use of the Dominion Police and later the RCMP, Canada repressed the labour movement and the political left in defense of capital. The collection focuses on three themes; the nineteenth-century roots of political policing in Canada, the development of a national security system in the twentieth-century, and the ongoing challenges associated with research in this area owing to state secrecy and the inadequacies of access to information legislation. This timely collection alerts all Canadians to the need for the vigilant defense of civil liberties and human rights in the face of the ever increasing intrusion of the state into our private lives in the name of countersubversion and counterterrorism. --Publisher's description
Keywords: Royal Canadian Mounted Police. Security Service -- History -- 20th century

Craft Capitalism: Craftsworkers and Early Industrialization in Hamilton, Ontario - Kristofferson, Robert B. (Canadian social history series, 2017)
Many studies have concluded that the effects of early industrialization on traditional craftsworkers were largely negative. Robert B. Kristofferson demonstrates, however, that in at least one area this was not the case. Craft Capitalism focuses on Hamilton, Ontario, and demonstrates how the preservation of traditional work arrangements, craft mobility networks, and other aspects of craft culture ensured that craftsworkers in that city enjoyed an essentially positive introduction to industrial capitalism. Kristofferson argues that, as former craftsworkers themselves, the majority of the city's industrial proprietors helped their younger counterparts achieve independence. Conflict rooted in capitalist class experience, while present, was not yet dominant. Furthermore, he argues, while craftsworkers' experience of the change was more informed by the residual cultures of craft than by the emergent logic of capitalism, craft culture in Hamilton was not retrogressive. Rather, this situation served as a centre of social creation in ways that built on the positive aspects of both systems. Based on extensive archival research, this controversial and engaging study offers unique insight to the process of industrialization and class formation in Canada. --Publisher's description. Contents: Introduction: Artisans, Craftsworkers, and Social Relations of Craft-Based Industrialization -- The Structure of Hamilton's Early Industrialization: Continuity and Change -- Personal Structures: Craftsworkers and Industrial Proprietors by 1871 -- Craft Mobility and Artisan-Led Industrialization: Continuity in Symbol and Practice -- A Culture in Continuity: Master-Man Mutualism in Hamilton, Ontario, during Early Industrialization -- The 'Self-Made Craftsworker': Transmodalism, Self-Identification, and the Foundations of Emergent Culture -- The 'Self-Improving Craftsworker': Dimensions of Transmodal Culture in Ideology and Practice -- Transmodal Culture in Apogee: 1872 Revisited -- Conclusion -- Notes -- Index.

Unions and the City: Negotiating Urban Change - MacDonald, Ian Thomas (ILR Press, an imprint of Cornell University Press, 2017)
Unions and the City serves as a road map toward both a stronger labor movement and a socially just urbanism. Focusing on four key economic sectors (film, hospitality, green energy, and child care), this book reveals that unions can exert a surprising level of influence in various aspects of urban policymaking.
Keywords: Community development, Urban; Community development, Urban New York (State) New York; Community development, Urban Ontario Toronto; Développement communautaire urbain New York (État) New York; Développement communautaire urbain Ontario Toronto; Labor movement; Labor movement New York (State) New York; Labor movement Ontario Toronto; Labor unions; Labor unions New York (State) New York; Labor unions Ontario Toronto; Mouvement ouvrier New York (État) New York; Mouvement ouvrier Ontario Toronto; New York (State) New York; Ontario Toronto; Sociologie urbaine New York (État) New York; Sociologie urbaine Ontario Toronto; Sociology, Urban; Sociology, Urban New York (State) New York; Sociology, Urban Ontario Toronto; Syndicats New York (État) New York; Syndicats Ontario Toronto

Policing Black Lives: State Violence in Canada from Slavery to the Present - Maynard, Robyn (Fernwood Publishing, 2017)
[This book] is a timely and much-needed exposure of historical and contemporary practices of state-sanctioned violence against Black lives in Canada. This groundbreaking work dispels many prevailing myths that cast Canada as a land of benevolence and racial equality, and uncovers long-standing state practices that have restricted Black freedom. A first of its kind, Policing Black Bodies creates a framework that makes legible how anti-Blackness has influenced the construction of Canada's carceral landscape, including the development and application of numerous criminal law enforcement and border regulation practices. The book traces the historical and contemporary mobilization of anti-Blackness spanning from slavery, 19th and 20th century segregation practices, and the application of early drug and prostitution laws through to the modern era. Maynard makes visible the ongoing legacy of a demonized and devalued Blackness that is manifest today as racial profiling by police, immigration agents and social services, the over-representation of Black communities in jails and prisons, anti-Black immigration detention and deportation practices, the over-representation of Black youth in state care, the school-to-prison pipeline and gross economic inequality. Following the dictums of the Black Lives Matter movement, Policing Black Bodies adopts an intersectional lens that explores the realities of those whose lives and experiences have historically been marginalized, stigmatized, and made invisible. In addressing how state practices have impacted Black lives, the book brings from margin to centre an analysis of gender, class, sexuality, (dis)ability, citizenship and criminalization. Beyond exploring systemic racial injustice, Policing Black Bodies pushes the limits of the Black radical imagination: it delves into liberatory Black futures and urges the necessity of transformative alternatives. --Publisher's description
Keywords: Blacks; Canada; Canada. Blacks; History. Blacks; History. Blacks. Blacks; Social conditions. Black Canadians; Social conditions. Race discrimination; Social conditions. Race discrimination. Race relations. Genre/Form: History. History

Blood, Sweat, and Fear: Violence at Work in the North American Auto Industry, 1960-80 - Milloy, Jeremy (UBC Press, 2017)
Going postal. We think of the rogue employee who snaps. But in [this book] Jeremy Milloy demonstrates that workplace violence never occurs in isolation. Using violence as a lens, he provides fresh and original insights into the everyday workings of capitalism, class conflict, race, and gender in the United States and Canada of the late twentieth century, bringing historical perspective to contemporary debates about North American violence. [The book] is the first full-length historical exploration of the origins and effects of individual violence in the automotive industry. Milloy’s gripping analysis spans 1960 to 1980, when North American auto plants were routinely the sites of fights, assaults, and even murders. He argues that the high levels of violence were primarily the result of workplace conditions – including on-the-job exploitation, racial tension, bureaucratization, and hypermasculinity – that made fear and loathing a shop-floor reality long before mass shootings attracted media attention in the 1980s. Workplace violence is typically the domain of management studies and psychology, but while we pass legislation and adopt best practices, the problem continues. Milloy’s explosive book reveals that workplace violence has been a constant aspect of class conflict – and that our understanding needs to go deeper. Blood, Sweat, and Fear will interest everyone concerned with the causes of workplace violence, and in particular scholars and students of labour history, sociology, sociological criminology, masculinity studies, and studies of race and of violence. --Publisher's description. Contents: Dripping with blood and dirt: confronting the history of workplace violence under capitalism -- Fights and knifings are becoming quite commonplace: Dodge main, 1965-80 -- The way boys and men took care of business: Windsor Chrysler plants -- The constant companion of all that earn their living here: workers, unions, and management respond -- Chrysler pulled the trigger: the courts and the press -- Out of the back streets and into the workplace: the discovery of workplace violence in the 1980s and 1990s.
Keywords: 20th century. Automobile industry and trade; 20th century. Automobile industry workers; 20th century. Violence; 20th century. Violence en milieu de travail; 20th century. Violence in the workplace; Aspect social; Canada; Conditions sociales; Histoire; History; Industrie et commerce; Social aspects; Social aspects. Genre/Form: History; Social conditions; United States; Violence in the workplace

An Exceptional Law: Section 98 and the Emergency State, 1919-1936 - Molinaro, Dennis G. (The Canadian social history series; Osgoode Society for Canadian Legal History, 2017)
During periods of intense conflict, either at home or abroad, governments enact emergency powers in order to exercise greater control over the society that they govern. The expectation though is that once the conflict is over, these emergency powers will be lifted. An Exceptional Law showcases how the emergency law used to repress labour activism during the First World War became normalized with the creation of Section 98 of the Criminal Code, following the Winnipeg General Strike. Dennis G. Molinaro argues that the institutionalization of emergency law became intricately tied to constructing a national identity. Following a mass deportation campaign in the 1930s, Section 98 was repealed in 1936 and contributed to the formation of Canada's first civil rights movement. Portions of it were used during the October Crisis and recently in the Anti-Terrorism Act of 2015. Building on the theoretical framework of Agamben, Molinaro advances our understanding of security as ideology and reveals the intricate and codependent relationship between state-formation, the construction of liberal society, and exclusionary practices. --Publisher's description. Contents: For the protection of people and state -- Defining suspects -- The trial -- Citizens of the world -- Outlaws -- Judgement.
Keywords: 20th century. War and emergency legislation. War and emergency powers. Mesures d'exception; 20th century. War and emergency powers; Canada; Histoire; History; War and emergency legislation

Precarious Employment: Causes, Consequences and Remedies - Procyk, Stephanie; Lewchuk, Wayne; Shields, John (Labour in Canada; 5, 2017)

Indians in the Fur Trade: Their Role as Trappers, Hunters, and Middlemen in the Lands Southwest of Hudson Bay, 1660-1870: with a new introduction - Ray, Arthur J. (Canada 150 Collection, 2017)
First published in 1974, this best-selling book was lauded by Choice as 'an important, ground-breaking study of the Assiniboine and western Cree Indians who inhabited southern Manitoba and Saskatchewan' and 'essential reading for anyone interested in the history of the Canadian west before 1870.' Indians in the Fur Trade makes extensive use of previously unpublished Hudson's Bay Company archival materials and other available data to reconstruct the cultural geography of the West at the time of early contact, illustrating many of the rapid cultural transformations with maps and diagrams. Now with a new introduction and an update on sources, it will continue to be of great use to students and scholars of Native and Canadian history. --Publisher's description

After Prison: Navigating Employment and Reintegration - Ricciardelli, Rose; Peters, Adrienne M.F. (Wilfrid Laurier University Press, 2017)
[This book] opens with a former prisoner's story of reintegration employment experiences. Next, relying on a combination of research interviews, quantitative data, and literature, contributors present an international comparative review of Canada's evolving criminal record legislation; the promotive features of employment; the complex constraints and stigma former prisoners encounter as they seek employment; and the individual and societal benefits of assisting former prisoners attain "gainful" employment. A main theme throughout is the interrelationship between employment and other central conditions necessary for safety and sustenance. [The] book offers suggestions for criminal record policy amendments and new reintegration practices that would assist individuals in the search for employment. Using the evidence and research findings of practitioners and scholars in social work, criminology and law, psychology, and other related fields, the contributors concentrate on strategies that will reduce the stigma of having been in prison; foster supportive relationships between social and legal agencies and prisons and parole systems; and encourage individually tailored resources and training following release of individuals. --Publisher's description. Contents: Section I – The Employment–Re-entry Enigma/Dilemma. Work after prison: one man's transition / James Young [pseudonym] -- Employment and desistance from crime / Kemi S. Anazodo, Christopher Chan, and Rose Ricciardelli -- Employment and criminal offenders with mental illness / Krystle Martin. Section II – Criminal Histories, Employment Prospects, and Moving Forward. Job search, suspended: changes to Canada's Pardon Program and the impact of finding employment / Samantha McAleese -- Vulnerabilities and barriers in post-release employment reintegration as indicated by parolees / Rose Ricciadelli and Taylor Mooney. Section III - Employment reintegration programming: supportive strategies and related outcomes. Is criminal history at the time of employment predictive of job performance? : A comparison of disciplinary actions and terminations in a sample of production workers / Mark G. Harmon, Laura J. Hickman, Alexandra M. Arneson, and Ashley M. Hansen -- Transforming rehabilitation: a critical evaluation of barriers encountered by an offender rehabilitation program for South Asian/Muslim offenders within the new probation service model / Christine Victoria Hough -- Promoting employment opportunities through mentorship for gang-involved youth reintegrating into the community / Adrienne M.F. Peters -- Barriers to community reintegration: the benefits of client-centred case management and pre-employment skills training / Ashley Brown. Section IV - The employment reintegration of unique populations. "Between a rock and a hard place": how being a "convict" hinders finding work in the neo-liberal, late-capitalist economy / Dale C. Spencer -- Does the "wrongful" part of wrongful conviction make a difference in the job market? / Kimberley A. Clow -- Conclusion. Employment reintegration / Rose Ricciardelli and Adrienne M.F. Peters.
Keywords: Canada. BUSINESS & ECONOMICS; Canada. Criminals; Employment; Employment. Genre/Form: Electronic books; Ex-convicts; Labor & Industrial Relations. Criminals; Labor. POLITICAL SCIENCE; Rehabilitation; Rehabilitation. Ex-convicts

Toutes les femmes sont d'abord ménagères : histoire d'un combat féministe pour la reconnaissance du travail ménager : Québec 1968-1985 - Robert, Camille (Collection Économie politique, 2017)
Dès les années 1970, le mouvement féministe québécois s’est largement mobilisé pour obtenir la reconnaissance sociale et économique du travail ménager. Toutefois, à partir des années 1980, cette lutte a été écartée, tant du mouvement des femmes que de son histoire. Combat abandonné, mais non gagné, son fardeau continue de peser aujourd’hui sur les femmes. Si la conciliation travail-famille ou la répartition des tâches dans le couple sont des thématiques présentes dans l’espace public, ce sont encore largement les femmes qui en assument la responsabilité. Ce livre propose une analyse historique des discours féministes sur le travail ménager et des débats entourant sa reconnaissance, à travers trois avenues : la socialisation, le salaire au travail ménager et les réformes gouvernementales. Rendre visible un travail qui ne l’est pas et réinscrire au sein des luttes féministes les enjeux liés à la reproduction sociale, tel est le but de cet ouvrage documenté et rigoureux. --Résumé de l'éditeur
Keywords: 1900-1999; Employés de maison Aspect économique Québec (Province); Employés de maison Québec (Province) Conditions économiques; Feminism; Feminism Québec (Province) History 20th century; Femmes au foyer Québec (Province) Conditions économiques; Féminisme Québec (Province) Histoire 20e siècle; History; Household employees Economic aspects Québec (Province); Household employees Québec (Province) Economic conditions; Housekeepers Québec (Province) Economic conditions; Housekeepers Salaries, etc. Québec (Province); Québec; Salaires Femmes au foyer Québec (Province); Wages Housewives; Wages Housewives Québec (Province)

Unions in Court: Organized Labour and the Charter of Rights and Freedoms - Savage, Larry; Smith, Charles W. (Law and society series (Vancouver, B.C.), 2017)
Since the turn of the twenty-first century, Canadian unions have scored a number of important Supreme Court victories, securing constitutional rights to picket, bargain collectively, and strike. Unions in Court documents the evolution of the Canadian labour movement’s engagement with the Charter, demonstrating how and why labour’s long-standing distrust of the legal system has given way to a controversial, Charter-based legal strategy. This book’s in-depth examination of constitutional labour rights will have critical implications for labour movements as well as activists in other fields. --Publisher's description.

As We Have Always Done: Indigenous Freedom Through Radical Resistance - Simpson, Leanne Betasamosake (Indigenous Americas, 2017)
Across North America, Indigenous acts of resistance have in recent years opposed the removal of federal protections for forests and waterways in Indigenous lands, halted the expansion of tar sands extraction and the pipeline construction at Standing Rock, and demanded justice for murdered and missing Indigenous women. In As We Have Always Done, Leanne Betasamosake Simpson locates Indigenous political resurgence as a practice rooted in uniquely Indigenous theorizing, writing, organizing, and thinking. Indigenous resistance is a radical rejection of contemporary colonialism focused around refusing the dispossession of Indigenous bodies and land. Simpson makes clear that the resistance's goal can no longer be cultural resurgence as a mechanism for inclusion in a multicultural mosaic. Instead, she calls for unapologetic, place-based Indigenous alternatives to the destructive logics of the settler colonial state, including heteropatriarchy, white supremacy, and capitalist exploitation. --Publisher's description.
Keywords: Activism. Ojibwa; Canada; Government relations; Government relations. Ojibwa Indians; Ojibwa Indians; Politics and government. Ojibwa; Politics and government. Ojibwa Indians

The Future of the Professions: How Technology will Transform the Work of Human Experts - Susskind, Richard E.; Susskind, Daniel (Oxford University Press, 2017)
This book predicts the decline of today's professions and describes the people and systems that will replace them. In an Internet society, according to Richard Susskind and Daniel Susskind, we will neither need nor want doctors, teachers, accountants, architects, the clergy, consultants, lawyers, and many others, to work as they did in the 20th century. The Future of the Professions explains how 'increasingly capable systems' -- from telepresence to artificial intelligence -- will bring fundamental change in the way that the 'practical expertise' of specialists is made available in society. The authors challenge the 'grand bargain' -- the arrangement that grants various monopolies to today's professionals. They argue that our current professions are antiquated, opaque and no longer affordable, and that the expertise of their best is enjoyed only by a few. In their place, they propose six new models for producing and distributing expertise in society. The book raises important practical and moral questions. In an era when machines can out-perform human beings at most tasks, what are the prospects for employment, who should own and control online expertise, and what tasks should be reserved exclusively for people? Based on the authors' in-depth research of more than ten professions, and illustrated by numerous examples from each, this is the first book to assess and question the relevance of the professions in the 21st century. --Publisher's description

Summer of My Amazing Luck - Toews, Miriam (https://www.penguinrandomhouse.ca/books/179092/summer-of-my-amazing-luck-by-miriam-toews/9780735274594, 2017)
Welcome to Winnipeg's Have-a-Life housing project... better known as Half-a-Life. Meet eighteen year-old Lucy and flamboyant Lish, two of the single moms who live there. Lucy has no idea who the father of her son is. Lish has four girls, and though she says she doesn't want a man around, she still pines for the father of her twins, a fire-eating busker who was just passing through town. Every Friday is "Deadbeat Dads" visiting day, but otherwise fathers aren't around much at Half-a-Life. Life at Half-a-Life has its ups and downs. The welfare regulations are endless and the ratfink neighbours won't mind their own business. Wagons and cheap strollers are the only way to get to and from the grocery stores, and it's hard enough to make ends meet without the welfare minister trying to take away the child tax credit. So when Lish decides they should go to Colorado to find the fire-eater, Lucy can't help but be excited. They borrow a van held together with coat hangers and electrical tape, load it up with kids and hit the road. Lucy knows they'll never find the fire-eater, but she doesn't know this will be the summer of her amazing luck. --Publisher's description
Keywords: Domestic fiction; Fiction; Humorous fiction; Logement social Romans, nouvelles, etc; Manitoba Winnipeg; Mères de famille monoparentale Romans, nouvelles, etc; Public housing; Public housing Fiction; Single mothers; Single mothers Fiction; Winnipeg (Man.) Fiction